From confrontation to co-operation: new security challenges facing post-apartheid Southern Africa - Monnakgotla, Kgomotso (Rhodes University, Faculty of Humanities, Department of Political Studies, 1998)
Trite as it may sound, the end of the Cold War is a landmark event in the history of human-kind. As such, this thesis was motivated by some of the international and local events that have taken place since the end of the 1980s. At the international level, the end of the Cold War has encouraged the re-examination of the concept of security. In Southern Africa too, this process has been strengthened by the demise of apartheid in South Africa. Initially challenged by a few academics, the traditional conception of security which perceived the threat to 'national' security primarily in the form of external military aggression no longer enjoys the primacy it was accorded during the Cold War era. A 'new' security discourse has emerged, and even though it has not yet made inroads into many governments' policy papers, there is some realisation that people's security concerns go beyond external military aggression to the state. Proponents of this 'new' thinking make reference to people-centred or human security - the notion that people and not the state, must be the objects of security. Arising from that, they point to the existence of many phenomena which should also be accorded security status especially in developing countries where people are confronted by life-threatening challenges such as disease, poverty, famine, and other challenges which do not necessarily threaten life, but if not tackled with urgency could transform themselves into the more conventional military threats. Here reference is made to the proliferation of small arms, political instability, mass migr?tions, and so on. In a region besotted by many of the challenges mentioned above, a security conception informed by the 'new' approach seems more appropriate. The outcome of the traditional approach to security is well known to the region many millions of lives were lost and it is estimated that billions of dollars in revenue were also lost, all in the name of maintaining the security of the South African state. Seeing neighbouring states as threats to its security because they accommodated liberation movements who occasionally instigated military attacks against Pretoria, the former apartheid state through its policy of 'Total Strategy' terrorised the entire region, including the majority of citizens within South Africa. However, since the end of apartheid in 1994, the new democratically elected South African government has committed itself to help build a politically stable, more secure, economically prosperous and integrated region. Through its accession to the Southern African Development Community (SADC), a body which it once tried to undermine, South Africa has further demonstrated a commitment to tackle some of the region's problems in unison with its former adversaries. Throughout the Southern African region there is a realisation that there are more long-term benefits to be gained by working together to tackle the challenges that confront almost all the countries in the region than trying to solve problems independently. Therefore through SADC, primarily a development-oriented body, Southern African states will also seek to address the region's security concerns. Many of the region's governments seem to show an understanding that security and development are intertwined - that they are two sides of the same coin whereby one cannot be attained without the other. Much as this understanding is laudable, in practice it does not seem as if it will translate to the prominence of so-called development issues or marginal security issues. Accepting the 'new' thinking on security also implies an acceptance of a wider range of security agents. It does not mean that by widening the agenda of security to include nonmilitary threats, more tasks will follow for the 'men' in uniform. What it means is that, the military establishment should no longer be the sole agent of security. Instead, where there is no military threat, resources should be channeled to other establishments such as those of health and research in order to fight the spread of AIDS. Furthermore, departments of water, environmental affairs, and so on, should be part of the security policy-making process. In addition, civil society should also be included in the policy-making process. Notwithstanding its limitations, and without undermining inter-governmental projects, civil society can at best promote security by serving as a watch-dog over policies adopted by governments. South Africa during the era of apartheid is a classic example of how governments cannot always be entrusted with the security of ordinary citizens. However, an examination of the structure and terms of reference of the newly created SADC Organ for Politics, Defence and Security (from henceforth referred to as the Organ) reflects a preponderance of the traditional/realist approach to addressing security concerns. It was conceived by, and is primarily constituted by the traditional establishments of security, that is, the military and the police. Some of the Organ's objectives include; security and defence cooperation through conflict prevention, management and resolution and mediation of disputes and conflicts. Nowhere is it evident that others besides those from a military/police background were involved in the formation of this important body. There is also no indication as to how other dimensions of security will be attained through the Organ. All this casts doubt regarding SADC's actual commitment to a development-oriented, people-centred and people-driven security. Nonetheless, current debates on security give hope to the notion that in the future, people's overall security needs will be addressed.
Keywords: Economic security -- Africa, Southern; Cooperation -- Africa, Southern; Africa, Southern -- Economic policy; Africa, Southern -- Foreign relations